Development of a core outcome set for the trials of complementary therapies in people with multiple sclerosis: international survey and consensus meetings - Viktor von Wyl; Jürgen Barth; Claudia M Witt; Francesco Pagnini; Jesus Lopez-Alcalde; Stefan Hägele-Link; L Susan Wieland; Francesco Nonino; Anna K Tietjen; Yuqian Yan; Claudia Canella; Nina Steinemann; et al. (BMJ Open)
Objectives This study aimed to develop a core outcome set (COS) for trials evaluating the effects of complementary therapies in people with multiple sclerosis (pwMS). We sought to identify the outcomes most relevant to pwMS, their relatives and friends, healthcare professionals and researchers and to propose these for inclusion in future trials.Design A participatory international research project using a mixed-method approach with qualitative and quantitative methods. The study included a scoping review and a national survey in Switzerland to identify candidate outcomes, followed by an international COS survey to rate the importance of these outcomes. The final phases involved two consensus meetings to refine and finalise the COS.Setting Data were sourced from the published literature and input from international stakeholders.Participants pwMS and other relevant stakeholders, including their relatives and friends, healthcare professionals and researchers.Results A total of 770 individuals participated in the international COS survey of 39 candidate outcomes (662 pwMS, 27 relatives/friends, 58 healthcare professionals and 23 researchers). According to the survey results, 13 outcomes were added to the COS, 5 were excluded and 21 were classified as ‘no consensus’. 13 individuals (six pwMS, one pwMS’s friend, three healthcare professionals and three researchers) attended the first consensus meeting. Following the voting on the outcomes without consensus, seven outcomes were added to the COS, four were excluded and 10 outcomes were still classified as ‘no consensus’. The six members of the stakeholders advisory board (one pwMS, four healthcare professionals and two researchers) attended the second consensus meeting to define the final COS. Nine additional outcomes were included in the COS. Sexual problems, an outcome previously excluded, were also added. In total, 30 outcomes were included in the final COS.Conclusion We have developed the first COS for future trials of complementary therapies for pwMS. The use of this COS will promote that future research in complementary therapies is relevant for pwMS and other stakeholders involved in MS care. Future COS research should integrate diverse geographical regions, where perspectives and access to complementary therapies may vary.Study registration number https://osf.io/ys7xt/.